Pengaruh Sistem Hidroponik Dan Media Tanam Terhadap Pertumbuhan Dan Produksi Tanaman Kembang Kol (Brassica oleraceae) - Abdul Rofik (Universitas Widya Gama Mahakam, 2016)
Effect of Hydroponic System and Growing Media on Growth and Production of Cauliflower (Brassica oleraceae). Results of analysis of variance showed that the influence of the hydroponic system very significant effect on plant height 8 ABP, 10 ABP. A high of 33.24 cm and 32.11 cm lows. number of leaves 8 ABP, ABP 12 with the highest value is 34.33 and the lowest 28.83. the flowering with the fastest value is 57.75 days and 76.50 days late, the diameter of the flower with the highest score is 71.32 grams and 64.05 grams lows. Hydroponic growing media influence a very significant effect on the number of leaves 4 ABP, ABP 6, and 8 weeks after planting. Significant effect on plant height 2 ABP, ABP 6, 8 ABP, ABP 12 with the highest score is 33.26 cm and the lowest was 32.42 cm, number of leaves 2 MST, MST 12 with the highest score is 34.08 and the lowest strand 29, 83 strands, the flowering with the fastest value is 75.75 days and 84.42 days late, flower diameter highest score is 71.15 mm and 61.51 mm and the weight the lowest rate that is the highest value and the lowest 43.82 53.65 grams g.interaction hydroponic system and growing media very significant effect on plant height 6 ABP with the highest value is 26.85 cm and 19.60 cm lows. Significant 2 ABP, 8 ABP, ABP 10, ABP 12 with the highest score is 33.75 cm and the lowest was 31.15 cm, number of leaves 2 ABP, ABP 4, 6 ABP, 8 ABP, ABP 10, ABP 12 with the highest score namely lows of 40.50 and 27.00, the fastest flowering with a value that is 67.00 days and 87.25 days late and a diameter of flowers with the best value and the lowest is 72.39 mm 53.35 mm.